Comparison of the pathological outcome and disease progression of two Mycobacterium caprae experimental challenge models in goats: endobronchial inoculation vs. intranasal nebulization - Melgarejo, Cristian; Cobos, Alex; Planas, Carles; Fondevila, Jaume; Martín, Maite; Cervera, Zoraida; Cantero, Guillermo; Moll, Xavier; Espada, Yvonne; Domingo, Mariano; Vidal, Enric; Pérez de Val, Bernat (Frontiers in Microbiology, 2023)
Goats are natural host of tuberculosis (TB) and are a valid animal model to test new vaccines and treatments to control this disease. In this study, a new experimental model of TB in goats based on the intranasal nebulization of Mycobacterium caprae was assessed in comparison to the endobronchial route of infection. Fourteen animals were divided into two groups of seven and challenged through the endobronchial (EB) and intranasal (IN) routes, respectively. Clinical signs, rectal temperature, body weight and immunological responses from blood samples were followed-up throughout the experiment. All goats were euthanized at 9 weeks post-challenge. Gross pathological examination, analysis of lung lesions using computed tomography, and bacterial load quantification in pulmonary lymph nodes (LN) by qPCR were carried out. The IN challenged group showed a slower progression of the infection: delayed clinical signs (body weight gain reduction, peak of temperature, apparition of other TB signs), as well as delayed immunological responses (IFN- peak response and seroconversion). At the end of the experiment, the IN group also showed significantly lower severity and dissemination of lung lesions, lower mycobacterial DNA load and volume of lesions in pulmonary LN, but higher involvement of the nasopharyngeal cavity and higher volume of the lesions in the retropharyngeal LN. The results indicated that the IN challenge with M. caprae induced pathological features of natural TB in lungs, respiratory LN and extrapulmonary organs, but extremely exaggerating the nasopharyngeal TB pathological features. On the other hand, the EB route oversized and accelerated the pulmonary TB lesion progression. Our results highlight the need to refine the inoculation routes in the interest of faithfully reproducing the natural TB infection when evaluating new vaccines or treatments against the disease.